Libro fotográfico sobre la memoria histórica y social de la plaza 24 de Mayo del centro histórico de Quito - Corella Gualoto, Gabriela Fernanda (2015)
In this study an investigation into the historical and social memory of the plaza May 24, as the first point photography was highlighted, the characters of the era of the twentieth century, urban legends and what the change was held transition that took the square from colonial times to the present. Second point emphasis on art, culture, cinema, theater accessories that are benefiting and highlighted in the data, recreational activities taking place in the square with the new change that came to be is now a boulevard. As a final point, surveys and interviews with residents of the sector were implemented, the data determined that the change observed is gratifying, therefore, people want to know and learn about their culture and identity. The observation made, helped a lot to know how he likes people informed of developments that have tourist attractions, therefore, the way to show this is through the photographic book that was done. The photo book is presented as a final product collects all important photos through history, with this you can know the whole evolution was obtained with the regeneration plan the metropolitan district of Quito has done. Currently Avenue May 24, is known as the Boulevard May 24, characterized as a cultural entertainment space for citizens and foreigners.